2001
DOI: 10.1038/sj.bmt.1702879
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of toxicity following two different doses of cyclophosphamide for mobilization of peripheral blood progenitor cells in 116 multiple myeloma patients

Abstract: Summary:High-dose cyclophosphamide (HDC) has been shown to be an effective regimen for collecting PBPC in multiple myeloma (MM) patients, but the optimal dose to be used remains controversial. Two historical cohorts of MM patients who received G-or GM-CSF and HDC at the dose of either 7 g/m 2 (HDC7, n = 74) or 4 g/m (HDC4, n = 42) were compared. As patients in the HDC4 group were more likely to have received G-CSF than GM-CSF (P Ͻ 10) and fewer previous alkylating agents (P = 0.004), multivariate logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 22 publications
2
60
0
3
Order By: Relevance
“…Desikan et al 29 reported increased hospitalization and transfusions in patients who underwent mobilization with G-CSF plus high-dose CY than with G-CSF alone. In addition, Jantunen et al 41 and Fitoussi et al 40 reported more hospital days, more days of i.v. antibiotics and more blood transfusions in patients who underwent mobilization with higher doses of chemotherapy than in those who received lower doses.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Desikan et al 29 reported increased hospitalization and transfusions in patients who underwent mobilization with G-CSF plus high-dose CY than with G-CSF alone. In addition, Jantunen et al 41 and Fitoussi et al 40 reported more hospital days, more days of i.v. antibiotics and more blood transfusions in patients who underwent mobilization with higher doses of chemotherapy than in those who received lower doses.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
“…Compared with mobilization regimens using G-CSF alone, chemomobilization is associated with increased morbidity, greater risk of infection, more hospital admissions, transfusions, antibiotic therapy and considerably greater cost overall. 29,[39][40][41][42] Although treatment-related mortality is rare, significant morbidity related to neutropenia that can often require hospitalization has been described, and many reports point to greater resource utilization with chemomobilization than with cytokine-alone mobilization. 29,37,39 Koc et al 39 found that although treatment with CY plus G-CSF resulted in greater stem cell yield than did treatment with GM-CSF plus G-CSF, it also caused greater morbidity.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy is very efficient for CD34 þ cells mobilization and may help to treat patient with MM, but is associated with several side -effects such as nausea, emesis, neutropenic fever, sepsis and hemorragic cystitis with mortality rates of 1-2%, and needs supportive care. [9][10][11] The VAD regimen is a polychemotherapy commonly used for patients with MM. [12][13] Combined to G-CSF, VAD administration displays the potential to mobilize PBSC with a theoretically reduced toxicity as compared to HD-CY.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-dose CY is associated with significant toxicity. 7,9 Recently, Fitoussi et al 9 showed that intermediate-dose CY (ID-CY) (4 g/m 2 ) plus growth factor was equally effective as high-dose CY in mobilising progenitor cells in myeloma patients but was less toxic.Mobilisation with CY 4 g/m 2 plus G-CSF is, however, also associated with significant toxicity and need for supportive care. We hypothesised whether low-dose CY (LD-CY) (up to 2 g/m 2 ) could be as effective and, less toxic mobilisation regimen in patients with newly diagnosed MM.…”
mentioning
confidence: 99%